Notes on aesthetic experience and everyday experience in John Dewey - Haubert, Laura Elizia (Cognitio-Estudos: revista eletrônica de filosofia, 2019)
The aesthetics developed by John Dewey relies on the philosopher’s effort to re-establish the broken bonds between life and art, thus demonstrating that aesthetic experience and everyday experience are intertwined and not completely different experiences. From this, Dewey also criticizes cultural institutions and museums as they were conceived, as they are responsible for strengthening this separation between art and life. This paper aims to clarify and show how Dewey re-establishes this bond and how it appears in his philosophy.